Student’s creative thinking ability in problem-posing activities viewed from self-efficacy - Husna, Insana Akmalul; Kurniasih, Ary Woro (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aims to determine the completeness of students' creative thinking abilities in knowing students' creative thinking processes in terms of self-efficacy, knowing students' responses to creative problem-solving learning with problem-posing activities, and knowing the obstacles experienced in learning. This research is a mixed-method with councurrent-embedded strategy. The sample of this study was one of class VIII in a Junior High School in Blora. The results showed that: (1) students' creative thinking skills with creative problem solving learning achieve mastery learning; (2) the description of the stages of students' creative thinking in terms of the level of self-efficacy that is on subjects who are in level of creative thinking ability 1 at the level of low and moderate self-efficacy is only able to pass the stage of synthesizing ideas and building ideas. Subjects at the level of creative thinking ability 2 at moderate and low levels of self-efficacy synthesize ideas and build ideas. Subjects at level of creative thinking ability 3 at moderate and high levels of self-efficacy are able to go through all stages of creative thinking, namely synthesizing ideas, building ideas, planning the application of ideas and applying ideas; (3) The use of creative problem solving learning models in which there are problem-posing activities get positive responses from students; (4) The obstacle experienced in this study is that this study when learning is used too much for group discussions.